If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -1(x + 7) = 36 Reorder the terms: -1(7 + x) = 36 (7 * -1 + x * -1) = 36 (-7 + -1x) = 36 Solving -7 + -1x = 36 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '7' to each side of the equation. -7 + 7 + -1x = 36 + 7 Combine like terms: -7 + 7 = 0 0 + -1x = 36 + 7 -1x = 36 + 7 Combine like terms: 36 + 7 = 43 -1x = 43 Divide each side by '-1'. x = -43 Simplifying x = -43
| 5y+50-8= | | 19.6+n=24.62 | | -20=f/2 | | 2t^2-30t+0=0 | | X/-9=-14 | | 17=-6-6x-1 | | -10x-2(12-5x)=-24 | | abs(3x-5)=abs(4x-2) | | 8-(x*x+7)=-35 | | .22(x+6)=.2x+5.3 | | x/3-9/4=x/6-1/2 | | 5v^2-17v=-6 | | 1/x=4/12 | | 8a-12=4(a-5) | | 6n^2+31n+18=0 | | 70m^2-73m+20= | | 2(x-8)=9 | | -2/3x=28 | | Q=j+jet | | X+78=x+41 | | -8=-2z+-14 | | 5y-6y+y+36=6y+30-2y | | 2u+6v=9 | | -3/4x=8/16 | | (255/256)/n | | √5/81 | | 0.9*x=180 | | 8x-3(x-1)=8x+21-2x | | -x-15+9x=3x+2+4y | | M/-4=1/16 | | 2y+3=4y+6 | | 3a+4b-2a+a+6b= |